Study on the Effectiveness of Integrating Religious Approaches in Health Interventions for Transgender Individuals in Malaysia - Mokhtar, Rafidah Hanim; Maliya Suofeiya; Draman, Samsul; Mohd Subri, Irwan; Syed Mohideen, Fathima Begum (IIUM Medical Journal Malaysia, 2025)
INTRODUCTION: Transgender women (mak nyahs) are biological males who self-identify as females and often face discrimination in education, employment, and healthcare. Economic marginalisation frequently pushes them into sex work, heightening risks of HIV infection, depression, anxiety, and substance abuse. While interventions for Muslim transgender communities exist, their effectiveness is underexplored. This study evaluated a health program integrating Islamic elements to reduce HIV-related risk behaviours among mak nyahs. MATERIALS AND METHOD: A cross-sectional study was conducted among 50 participants recruited via respondent-driven sampling. A validated, self-administered questionnaire assessed religiosity and HIV-related risk behaviours. The intervention, delivered in a 3-day, 2-night motivational camp (Mukhayyam), incorporated Islamic talks, tazkirah (religious reminders), songs, videos, slides, and quizzes. Participants completed questionnaires at baseline (Day 1) and post-intervention (Day 3). RESULTS: The mean age of respondents was 39.9 years (SD=9.46). One-fifth reported sex work, and only one-third reported no HIV-related sexual risk behaviours. The intervention significantly improved knowledge and attitudes related to ibadah (z=-2.317, p=0.021) and akhlak (z=-2.900, p=0.004), with an overall increase in Islamic religiosity scores (z=-3.038, p=0.002). Health knowledge also improved, particularly on the negative effects of cosmetic procedures (z=-2.848, p=0.004). CONCLUSION: The Mukhayyam-based intervention incorporating Islamic teachings enhanced religious knowledge and showed potential in reducing HIV-related risks among Muslim transgender women. Longitudinal studies and controlled trials are warranted to evaluate sustainability and scalability.